2020
DOI: 10.1002/slct.202003479
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Nucleotide Pyrophosphatase/Phosphodiesterase Inhibition Studies of Carbohydrazides Based on Benzimidazole‐Benzothiazine Skeleton

Abstract: Ecto‐nucleotide pyrophosphatases/phosphodiesterases (ENPPs) are important family of ecto‐nucleotidases. There are seven members of ENPP family out of which ENPP1 and ENPP3 hydrolyze nucleotides whereas, ENPP2 preferably hydrolyzes phospholipids as compared to nucleotides. Overexpression of ENPP1 and ENPP3 has been reported to be associated with many health disorders such as diabetes, chondrocalcinosis, osteoarthritis, and cancer. Development of ENPP1 and −3 inhibitors might be useful for the treatment of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…In another study, two molecules, 1,3-disubstituted-benzimidazole-2-imine ( 433 ) and 1,3-thiazolo[3,2- a ]benzimidazolone derivative ( 434 ), exerted dual effects against dipeptidyl peptidase-IV (DPP-IV) and xanthine oxidase (XO) enzymes with IC 50 values less than 200 μM ( Tomovic et al, 2020 ). Finally, Kanwal et al ( Kanwal et al, 2020 ) prepared a library of benzimidazole-benzothiazine hybrid molecules by Gabriel–Colman rearrangement of methyl 2-(1,1-dioxido-3-oxobenzo[ d ]isothiazol-2(3 H )-yl) acetate, and reported that compounds 435–436 exhibited potential antidiabetic property by inhibiting Ecto-nucleotide pyrophosphatases/phosphodiesterases 1 (ENPP1) 1 and -3.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…In another study, two molecules, 1,3-disubstituted-benzimidazole-2-imine ( 433 ) and 1,3-thiazolo[3,2- a ]benzimidazolone derivative ( 434 ), exerted dual effects against dipeptidyl peptidase-IV (DPP-IV) and xanthine oxidase (XO) enzymes with IC 50 values less than 200 μM ( Tomovic et al, 2020 ). Finally, Kanwal et al ( Kanwal et al, 2020 ) prepared a library of benzimidazole-benzothiazine hybrid molecules by Gabriel–Colman rearrangement of methyl 2-(1,1-dioxido-3-oxobenzo[ d ]isothiazol-2(3 H )-yl) acetate, and reported that compounds 435–436 exhibited potential antidiabetic property by inhibiting Ecto-nucleotide pyrophosphatases/phosphodiesterases 1 (ENPP1) 1 and -3.…”
Section: Biological Activitiesmentioning
confidence: 99%
“… 21 In the previous study, we have reported pyrrolo[2,3- b ]pyridine derivatives such as ( N -(pyrrolo[2,3- b ]pyridine-1-carbonyl)benzenesulfonamide), which was found as a selective inhibitor of ENPP1 with an IC 50 value of 4.50 ± 0.16 μM and carbohydrazide-based derivative, which selectively blocked the activity of ENPP3 to half of the maximal value of 0.15 μM. 22 , 23 Various previously reported structures with sulphonate scaffolds including raloxifene sulphonates, benzofuran, and benzothiophene sulphonates exhibited significant enzyme inhibitory activity to sub-micromolar levels, for example, raloxifene sulphonate derivative 3-(4-(2-(piperidin-1-yl)ethoxy)benzoyl)-2-(4-(tosyloxy)phenyl)benzo[ b ]thiophen-6-yl-4-methylbenzenesulfonate tabulated selective inhibition of isozyme ENPP1 to an IC 50 value of 0.45 μM, and benzothiophene derivative (4-(benzo[ b ]thiophen-5-yl)phenyl cyclohexanesulfonate) was endowed with IC 50 = 0.12 μM against ENPP1 and 1.89 μM toward ENPP3. 24 , 25 We have also reported sulphonate derivatives mainly based on non-aromatic or saturated cyclic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%